Loureirin B Exerts its Immunosuppressive Effects by Inhibiting STIM1/Orai1 and KV1.3 Channels - Shi, Shujuan; Zhao, Qianru; Ke, Caihua; Long, Siru; Zhang, Feng; Zhang, Xu; Li, Yi; Liu, Xinqiao; Hu, Hongzhen; Yin, Shijin (Frontiers in Pharmacology, 2021)
Loureirin B (LrB) is a constituent extracted from traditional Chinese medicine Resina Draconis. It has broad biological functions and has an impressive immunosuppressive effect that has been supported by numerous studies. However, the molecular mechanisms underlying LrB-induced immune suppression are not fully understood. We previously reported that LrB inhibited KV1.3 channel and inhibited calcium ion (Ca2+) influx and interleukin-2 (IL-2) secretion in Jurkat T cell. In this study, we applied CRISPR/Cas9 to edit KV1.3 coding gene KCNA3 and successfully generated a KV1.3 knockout (KO) cell model to determine whether KV1.3 KO was sufficient to block the LrB-induced immunosuppressive effect. Surprisingly, we showed that LrB could still inhibit Ca2+ influx and IL-2 secretion in the Jurkat T cells in the absence of KV1.3 although KO KV1.3 reduced about 50% of Ca2+ influx and 90% IL-2 secretion compared with that in the wild type cells. Further experiments showed that LrB directly inhibited STIM1/Orai1 channel in a dose-dependent manner. Our results suggest that LrB inhibits Ca2+ influx and IL-2 secretion in Jurkat T cells by inhibiting both KV1.3 and STIM1/Orai1 channels. These studies also revealed additional molecular target for LrB-induced immunosuppressive effect, which makes it a promising leading compound for treating autoimmune diseases.